A visual analysis of HIV/AIDS antiretroviral therapy print campaign materials found in four Western Cape community clinic environments - Murray, Jacqueline Ruth (Centre for Film and Media Studies, 2017)
Print media campaign material strongly influences people's perceptions of illness and health and the role and purpose of medication (NSMC, 2010: np). Because adherence is critical to the successful management of the Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS), the introduction of antiretroviral treatment (ART) into the South African health sector presented a major communications challenge, namely how best to communicate awareness and administration of the drugs and how they should be taken. Over the past ten years, the government Department of Health (DoH), the Treatment Action Campaign (TAC), and other prominent nongovernmental HIV/AIDS organizations (NGOs) such as Love Life, Soul City and the Bishop Tutu Foundation have defined a number of different objectives aimed at the promotion of prescription generic antiretroviral drugs (Venter, 2014:3). This has led to an increase in the number of campaigns, each having singular visual representations of HIV/AIDS and users' relationships to antiretroviral drugs. Despite this, stigma and distrust around HIV/AIDS is prominent among the South African public (Rubincam, 2013:13). As a result, there remains a large amount of ambivalence toward the impact of ART on the body and its place within many communities. This has a direct bearing on issues of adherence. For this reason, it is important to study the nature and efficacy of the materials currently being used for social marketing in this context. This qualitative study therefore questions the nature of the current visual language of ART related leaflets and posters found in four Western Cape community clinics and asks whether the content effectively communicates an understanding of antiretroviral therapy, specifically around issues of adherence. In this study, I aim to identify ART adherence social marketing communication strategies used by leading NGOs and the DoH in South Africa. The nature of the visual and textual representations of antiretroviral print media campaign materials found in four Western Cape community clinic environments is established. The purpose of this research is to provide contemporary and useful information on the style, content, and design of social marketing materials in the hope that it will add significant value for further research on ART adherence. This study is a microanalysis focused on quality, not quantity. The investigation is modest. It does not consider a large sample and is intended as a starting point for further research. I hope to identify possible gaps between the combination of messages offered in leaflet and poster print media, and the needs of those infected with the virus, especially at a time when it necessitates they begin ART. The intended impact of this research is to encourage an increased understanding and awareness by government and NGO marketing departments of their campaign material so that it facilitates the transition onto treatment in a way that is empowering, informative, empathetic, and responsible.